2015
DOI: 10.15823/p.2015.02
|View full text |Cite
|
Sign up to set email alerts
|

Difficulties Experienced by Prospective Teachers of Psychology during the Teaching Practice

Abstract: 1Lietuvos edukologijos universitetas, Ugdymo mokslų fakultetas, Raidos ir ugdymo psichologijos katedra, Studentų g. 39, 08106 Vilnius, tomas.lazdauskas@leu.lt 2 Lietuvos edukologijos universitetas, Ugdymo mokslų fakultetas, Raidos ir ugdymo psichologijos katedra, Studentų g. 39, 08106 Vilnius, albina.saikauskiene@leu.lt Anotacija. Straipsnyje pristatoma būsimųjų psichologijos mokytojų pedagoginės praktikos refleksijų analizė. Refleksijoms analizuoti pasirinkta teminė analizė, analizės vienetas -pedagoginės pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Research done in Lithuania more than a decade ago (Bulajeva, 2000) showed that the main subjects lacking in future teachers are higher self-esteem, dignity, abilities to manage emotions, develop positive attitudes, overcome tension, anxiety, constructively resolve conflicts and emerging problems. Nevertheless, lately, future teachers are experiencing emotional difficulties due to lack of social competence, which can lead to the failure of the whole educational process (Lazdauskas, Saikauskiene, 2015). It has been suggested (Becker et al, 2014;Lazdauskas, Saikauskiene, 2015) that the feelings experienced by the teacher during a lesson are affected by the emotions experienced by the students.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research done in Lithuania more than a decade ago (Bulajeva, 2000) showed that the main subjects lacking in future teachers are higher self-esteem, dignity, abilities to manage emotions, develop positive attitudes, overcome tension, anxiety, constructively resolve conflicts and emerging problems. Nevertheless, lately, future teachers are experiencing emotional difficulties due to lack of social competence, which can lead to the failure of the whole educational process (Lazdauskas, Saikauskiene, 2015). It has been suggested (Becker et al, 2014;Lazdauskas, Saikauskiene, 2015) that the feelings experienced by the teacher during a lesson are affected by the emotions experienced by the students.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, lately, future teachers are experiencing emotional difficulties due to lack of social competence, which can lead to the failure of the whole educational process (Lazdauskas, Saikauskiene, 2015). It has been suggested (Becker et al, 2014;Lazdauskas, Saikauskiene, 2015) that the feelings experienced by the teacher during a lesson are affected by the emotions experienced by the students. The scope of teaching practice in 2001 was 17 credits and in 2018 -20 credits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation